CONSEQUENCES OF INFORMATION CONTROLLABILITY THROUGH AUGMENTED REALITY AT THE POINT OF SALE: AN ANALYSIS - Faisal, Ijang; Dwika Ayu Amrita, Nyoman; Aripin, Zaenal (KRIEZ ACADEMY : Journal of development and community service, 2024)
The use of augmented reality (AR) at the point of sale has become an innovative strategy in improving consumer experience and influencing purchasing decisions. However, challenges related to the consistency and reliability of information presented through AR require special attention from sellers. In this discussion, we explore the impact and challenges of information controllability through AR on consumer perceptions, purchasing decisions, and sales strategies. Positive impacts include increased consumer engagement, increased perception of product value, and reduced purchase uncertainty. However, challenges such as technical errors, complex content management, and building consumer trust require a holistic, team-based approach to overcome. Recommended strategies include thorough testing of AR applications, use of monitoring technology, integration of AR into sales operations, careful content management, and transparent communication with consumers. By overcoming these challenges, sellers can harness the full potential of using AR to increase consumer engagement, strengthen brand image, and increase sales.